Reality of the redeployment of Algerian banks During the Economic transition phase - LELLOUCHI , Mohamed (Dirassat Journal Economic Issue, 2017)
The theme treated by this article concerns the reality of the redeployment of Algerian banks during the economic transition phase that the country is currently going through and which is characterized by profound transformations in the banking and financial environment (internationalization and diversification of banking activity) with an increasingly rigorous application of prudential regulation which thus becomes inevitable for effective management of banking risks and finally the opening of the banking sector to private capital.